Neutron strain scanning of fibre and diode laser welds in stainless steel and Ti6Al4V - Voisey, K.T.; Folkes, J.; Srithorn, J.; Hughes, D.J. (Elsevier, 2014)
Fibre lasers provide an unprecedented combination of high beam quality, brightness and low cost. Fibre laser beams can provide an exceptionally high power density beam with a relatively large depth of focus. Compared to more established laser welding technologies such as diode laser welding, fibre laser welding produces exceptionally narrow weld beads. As with all types of welding, fibre laser welding produces residual stresses in the material forming and adjacent to the weld. The SALSA instrument at the Institut Laue Langevin (ILL) has been used to make neutron diffraction measurements for both fibre and diode laser welded stainless steel 304 and Ti6Al4V. Clear diffraction peaks are obtained from stainless steel 304 and residual stress distributions are obtained. Little variation in residual stress distribution with welding parameters is seen. Ti6Al4V diffraction peaks are complicated by phase transformations on cooling. Transformed beta phase peaks in Ti6Al4V allow the extent of the heat affected zone to be determined.